Gender bias in education in Burkina Faso: Who pays the piper? Who calls the tune? - Some Touorouzou (Journal of Contemporary Issues in Education, 2006)
In this chapter, I analyze policies developed by the government of Burkina Faso in order to redress an imbalance in gender education. Girls, in effect, are not getting their fair share of education, whether in quantity or quality. I critique existing policies concerning gender issues in education by first taking stock of different policies launched in favor of the education of girls, the context of their formation, and identify shortcoming therein. It has been found that international organizations, beyond their commitment to reverse the lag in the education of girls, bring with them an agenda that is at times contradictory with the aim of education for all. At the same time that governments are prodded to school all girls, Structural Adjustments Programs that generally bring more poverty and less public spending, are at loggerheads with increased access. Moreover, the policy choices of international organizations seem to be ill-equipped to subvert existing ideological and patriarchal structures. These structures do not allow for the empowerment of women. The government itself is found to have very little leverage on current policies, raising the nagging question of their appropriation.